Analysis of Total Phenol Levels in Moringa Extract (Moringa Oliefera Lamk.) in Vegetable Oil - Mahmudah, Rif’atul; Muslimah; Yulianti, Eny (Al-Kimia, 2023)
Vegetable oil extract moringa leaf (Moringa Oleifera Lamk.) is an herbal oil that has the potential as a medicine. The study aimed to determine the content of secondary metabolites through photochemical tests and the total phenol content of Moringa leaf extract in extra virgin olive oil and virgin coconut oil. The extraction method used is hot maceration with various doses of Moringa leaves. The best amount is used by extraction with variations in temperature and heating time. The functional groups of herbal oils were identified using an FTIR spectrophotometer. Phytochemical test results showed that the vegetable oil extract of Moringa leaf contains secondary metabolites in the form of flavonoids, phenolics, terpenoids, alkaloids, steroids, and tannins. The highest total phenol content in Moringa leaf extract in virgin olive oil at a concentration of 40%, extraction temperature 50°C with a heating time of 2 hours with a total phenol content value of 15.78% GAE (Gallic Acid Equivalent). The results of the FTIR interpretation show that herbal oils have O-H, C-H, C=O, C=C aromatic, C-O, and aliphatic C-H functional groups.